Strategizing in the context of opportunities = Strategizowanie w kontekście okazji - Sus, Aleksandra (Zielona Góra: Faculty of Economics and Management Press)
This article attempts to draw attention to exploiting opportunities by strategists. The paper consists of four parts. The first one introduces the reader to the strategizing approach and macro-and micro-level strategic analysis.
Keywords: strategizowanie; okazja; mikropodstawy; niepewność; behawioryzm; strategizing; opportunity; microfoundations; uncertainty; behaviourism